Bovine viral diarrhea virus infections in pigs: why is this situation important for Brazilian herds? - Almeida, Henrique Meiroz De Souza; Gatto, Igor Renan Honorato; Santos, Anne Caroline Ramos Dos; Pereira, Daniele Araujo; Nascimento, Karla Alvarenga; Baraldi, Thaís Gasparini; Mechler, Marina Lopes; Oliveira, Luís Guilherme De (Instituto Biológico, 2017)
ABSTRACT: Swine can be infected by the bovine viral diarrhea virus (BVDV) under natural conditions. For this reason, further information and divulgation are needed regarding the pathogenicity of this virus in swine. This infection is practically unknown in the realm of pig farming, and, as it shares some similarities with the classical swine fever virus (CSFV), its diagnosis becomes a challenge for official sanitary programs. Studies have shown the absence of clinical signs in piglets and reproductive problems in sows due to BVDV infections. There is little research on the prevalence, risk factors, preventive measures and control of BVDV in pigs around the world. And in Brazil, the data is practically non-existent. At the time of diagnosis, comparing the most efficient laboratory tests such as virus neutralization, ELISA, RT-PCR, and immunofluorescence so as to minimize the risk of cross serological reactions when dealing with a persistent or transient infection, can be an important tool. Moreover, the practical implications for CSFV eradication programs are a main reason for the development of further research against this infection. Therefore, this paper aims to review various aspects of BVDV infection in pigs, and how this information can be important for Brazilian herds.

RESUMO: O suíno pode ser infectado pelo vírus da diarreia viral bovina (BVDV) em condições naturais, por isso são necessárias maiores informações e mais divulgação sobre a ação deste vírus nos suínos. Esta infecção é praticamente desconhecida na suinocultura e, devido a algumas semelhanças com vírus da peste suína clássica (VPSC), torna-se um desafio para os programas sanitários oficiais. Estudos revelam a ausência de sinais clínicos em leitões ao mesmo tempo em que evidenciam problemas reprodutivos em porcas devido à infecção do BVDV. Poucas são as pesquisas sobre a prevalência, fatores de riscos, medidas de prevenção e controle do BVDV em suínos no mundo e, no Brasil, os dados são praticamente inexistentes. No diagnóstico, comparar os exames laboratoriais mais eficientes como a virusneutralização, ELISA, RT-PCR e imunofluorescência, diante de uma infecção persistente ou transitória, e assim minimizar o risco de reações sorológicas cruzadas pode ser uma ferramenta fundamental. Ademais, as implicações práticas em programas de erradicação da PSC são um grande motivo para o desenvolvimento de mais pesquisas frente a esta infecção. Portanto, este trabalho pretende revisar diversos aspectos da infecção do BVDV em suínos evidenciando o quanto essa situação pode ser importante para os rebanhos brasileiros.
A infecção pelo vírus da diarreia viral bovina em suínos: por que essa situação é importante para os rebanhos brasileiros?
Keywords: swine production; bovine viral diarrhea virus; pathogenesis; animal health protection; classical swine fever virus; suinocultura; vírus da diarreia viral bovina; patogenia; defesa sanitária animal; vírus da peste suína clássica